The problems of gender equality in the labor market (Nobel Prize, 2023) - Shymanska, Oksana (Herald of Economics, 2024)
Introduction. Gender equality in the labor market, which implies equal rights for men and women in terms of employment opportunities and wages, has become the subject of active discussions in scientific circles. Overcoming gender inequality in the labor market is a guarantee not only of the harmonious development of a professional career and the creation of equal conditions for all employees, regardless of gender, but also of increasing the efficiency of the labor force uses. The research of the 2023 Nobel laureate in Economics, Claudia Goldin, actualized the need for a more detailed study of the problem, in particular given the fact that under the conditions of war in Ukraine, changes in the dynamics of women’s participation are taking place both in social and political processes that require making important decisions, and in the market labor in general. Purpose of the article – to substantiate the contribution of K. Goldin, laureate of the 2023 Nobel Prize in Economics, to the development of economic science in the context of building a model of gender equality in the labor market. Methods. During the preparation of the article, general scientific methods of research were used: analysis, synthesis, induction, deduction, mathematical methods, which contributed to the greatest extent to the understanding of K. Goldin’s scientific views on the problem of gender equality in the labor market. Results. The contribution of the 2023 Nobel laureate in Economics, K. Goldin, to the understanding of the “theory of discrimination”, according to which men and women have different actual and imaginary qualification characteristics, which serve as the basis for the emergence of gender inequality in the labor market, was substantiated. Discrimination can increase differences in the professional competences of employees or lead to their appearance in the case of career growth, if some of them are more visible than others. The historical nature of the model of gender inequality in the labor market proposed by K. Goldin, which is hidden in past experience and has an impact on the current situation within the studied market, was revealed. The dynamic development of the economics, technological changes, which led to the narrowing of the minimum level of competences necessary for the performance of professional functions, in the historical context led to the appearance of women in the labor market, which, at the same time, served as a signal for changing the standards of professions. A key feature of the model proposed by K. Goldin is the information asymmetry, in which the society does not know the level of productivity of a specific job applicant. Based on this, her admission to the profession will “contaminate” the status of existing male workers in it. This kind of prejudice can be eliminated by introducing mechanisms for transparent attestation of professions. Most professions are not inherently male or female. Mostly, the “aura of gender” arises due to rhetoric related to the perception of established norms regarding the use of certain forms of physical capital. In the research process, one of the aspects of discrimination in women’s wages was revealed, which is related to the rejection of piece-work contracts in favor of monthly wages for employees who work for a long time. It was established that in the case of differences in physical strength, endurance or intensity of work, there are prerequisites for the acquisition of “secondary sexual characteristics” by professions. Discussion. K. Goldin’s scientific contribution serves as a basis for further research into gender problems in the labor market, which may be caused by various factors depending on the period of social development. In particular, Ukraine today is actively developing national qualification standards in accordance with European requirements, promoting digital development and expanding opportunities for women in the labor market. 2023 Nobel Laureate in Economics Claudia Goldin’s research overall provides a better understanding of the historical context of labor markets, as well as what they are today and where they will be in the future.